La música que des-cubre el silencio: Pedagogías decoloniales para la educación musical de personas sordas - Otero Caicedo, Liliana Elizabeth (CALLE14: revista de investigación en el campo del arte, 2021)
We have naturalized the “limitation” of deaf people to such an extent that, from the music education field there are few offerings to defend music as a fundamental human right. Furthermore, the binary fundamentalisms of deficiency/capacity, normal/abnormal, hearing/deaf, constitute a colonial horizon that overpowers deaf people, nullifying their ‘sound being’ under the dominant assumptions of the ideology of normality. From decolonial pedagogies, the musical experience is understood as an aesthetic-political-pedagogical practice that should cause fractures in the hegemonic understanding of this auditory art, enabling a decolonization of sound that accrues in the recognition of the musical capital that the deaf community has, and thus, understand the auditory difference as the opportunity to discover other musical worlds that legitimize the possible innate skills, the intercultural experiences and the interests in the musical field of those who inhabit silence.